Perspective on Epithelial-Mesenchymal Transitions in Embryos - McClay, David R (Methods Mol Biol, 2021)
The epithelial-mesenchymal transition (EMT) is a key process required for building the early body plan of metazoa. It involves coordinated and precisely timed changes in multiple cell processes such as de-adhesion, motility, invasion, and cell polarity. While much has been learned about how embryos deploy epithelial-mesenchymal transitions since Betty Hay named the process decades ago, a number of things are still not well understood. Here I will discuss some of the big questions that remain, including how is all of this controlled, how does each of the cell biological events work, and how are they so nicely coordinated with one another?